Conventional and synchrotron-based x-ray studies for characterization of soil symbionts - Bamberg, Soraya Marx (2019)
Nitrogen-fixing bacteria (NFB) in symbiosis with legumes form structures called nodules that increase the N fixation efficiency. Arbuscular mycorrhizal fungi (AMF) are known by their efficiency in obtain P available to plants. The triple symbiosis between legumes, FMAs, and NFB is denominated tripartite. In the tripartite symbiosys the nodule formation protects the NFB, the AMF provide P to the system, and the legumes provide photoassimilates for both symbionts. In view of the nutritional benefits of these relationships the thesis aims are to evaluate the nutritional status of the tripartite association microorganisms and to identify the possible AMF mechanisms in the absorption and compartmentalization of Se in their spores, as a possible strategy to the plant protection. In the first study lima-bean (Phaseolus lunatus L. Walp) was cultivated in pots, to which were added AMF isolates (Glomus macrocarpum and Acaulospora colombiana) and NFB (Bradyrhizobium japonicum), also control plants were added. The quantification of the mineral elements in the tripartite symbiosis components was performed using X-ray dispersive energy spectroscopy (EDX), and scanning electron microscopy (SEM) was used to identify structures. The second study was conducted with Brachiaria decumbens (Urochloa decumbens) cultivated for 30 days in pot, using AMF isolates (Acaulospora morrowiae, Dentiscutata heterogama and Rhizophagus clarus), uninoculated control plants, and five doses of sodium selenate (0.2 , 4, 6 and 8 mg kg -1Se). A parallel experiment was conducted on agar medium using Petri dishes with the same Se doses from the pot experiment, which allowed seven spores of Dentiscutata heterogama fungi to grow for 15 days at 37 °C. Mycorrhizal colonization and the Se in shoot plant accumulation were evaluated, as well as the quantification and visualization of Se in the AMF structures by microanalyses of synchrotron X-ray fluorescence (S-XRF). EDX analysis detected 13 elements, showing the occurrence in all tissues, roots, epidermis and nodules. The distribution of the elements in the bean was related to its symbiosis function. The fungi reached high colonization rates in the brachiaria plants. The Se accumulation in shoot plants indicated a possible protective effect provided by R. clarus in U. decumbens to avoid Se accumulation. The S-XRF analysis identified Se in a vesicle of R. clarus within a root fragment, and also, Se presence in D. heterogama spores germinated in Petri dish. In view of the thesis studies, the SEM-EDX and S-XRF techniques were efficient for the soil symbionts characterization allowing a scientific contribution of applicability of these microorganisms.